Geriatric intensive care Consensus paper of DGIIN, DIVI, DGAI, DGGG, oGGG, oGIAIN, DGP, DGEM, DGD, DGNI, DGIM, DGKliPha and DGG - Michels, Guido; Sieber, Cornel; Marx, Gernot; Roller-Wirnsberger, Regina; Joannidis, Michael; Mueller-Werdan, Ursula; Muellges, Wolfgang; Gahn, Georg; Pfister, Roman; Thuermann, Petra A.; Wirth, Rainer; Fresenborg, Jana; et al. (Zeitschrift für Gerontologie und Geriatrie, 2019)
The proportion of elderly, frail, and multimorbid people has increased dramatically in recent decades resulting from demographic changes and will further increase, which will impact acute medical care. Prospective, randomized studies on geriatric intensive care are still lacking. There are also no international or national recommendations regarding the management of critically ill elderly patients. Based on an expert opinion, this consensus paper provides 16 statements that should be considered when dealing with geriatric critical care patients.
CRIS-Team WoS Importer:2019-09-03